2020
DOI: 10.1177/2475530320910814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Genetic Risk Score for Diagnosis of Psoriatic Arthritis

Abstract: Background: Diagnosis of psoriatic arthritis (PsA) can be challenging, resulting in delays that contribute to irreversible joint damage, reduced quality of life, and increased mortality. Objective: Use genetic markers to develop and evaluate a PsA genetic risk score (GRS) for its ability to discriminate between psoriasis (PsO) only and PsO with PsA among a psoriatic cohort with full genome-wide genotype data. Methods: Genome-wide single-nucleotide polymorphism genotyping was performed on 724 psoriatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our prediction models showed only modest ability to discriminate PsA from PsC in the available data sets, which was consistent with the findings of a recently published study by Smith et al (26). For the first approach, we attempted to reproduce a previously published classification pipeline by following the description and published model parameters, which allowed us to reproduce the workflows (13).…”
Section: Discussionsupporting
confidence: 92%
“…Our prediction models showed only modest ability to discriminate PsA from PsC in the available data sets, which was consistent with the findings of a recently published study by Smith et al (26). For the first approach, we attempted to reproduce a previously published classification pipeline by following the description and published model parameters, which allowed us to reproduce the workflows (13).…”
Section: Discussionsupporting
confidence: 92%
“…Human Leucocyte Antigen (HLA) was studied in 6 publications ( 19 , 27 29 , 35 , 36 ). A family-based study reported an association between PsA and various HLA alleles: HLA-B*27, HLA-B*38, HLA-B*39, and HLA-C*12 ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…After applying the eligibility criteria of this systematic review to the full texts of the 14 studies, only five studies were included in the review [6,[9][10][11][12]. The reasons for the exclusion of the eight studies are listed in Table 1 [4, [13][14][15][16][17][18][19][20].…”
Section: Results Of Searchmentioning
confidence: 99%